Aspidistra dahuaensis (Asparagaceae), a new species from Guangxi, China - Nong, Dong-Xin; Peng, Yu-De; Ke, Fang; Yu, Li-Ying (Phytotaxa, 2020)
Aspidistra dahuaensis, a new species discovered in west-central Guangxi, China, is described and illustrated. This new species has widely bowl-shaped perigone and is easily distinguished from other congeners by its unique stigma, which is deeply 3–4-lobed at the center, with lobes that are very thin and explanate, with the margin that is slightly rolled up, and each apex lobe is shallowly 3-lobed again.